Survei minat siswa dalam pembelajaran permainan sepak bola di kelas VIII SMP Negeri 3 Patokbeusi - Mudabighy, Reihan Ahmad; Iqbal , Rahmat; Salam Hidayat , Abdul (Jurnal Porkes, 2024)
This study aims to assess student interest in learning soccer games in class VIII SMPN 3 Patokbeusi. The method used was survey method with quantitative descriptive approach. The study population included all VIII grade students of SMP Negeri 3 Patokbeusi, Subang Regency, totaling 169 students with sampling techniques using total sampling, namely taking all the population into the sample. The instrument used in this research used a questionnaire with 41 statement items with internal and external indicators. The data analysis technique in this study used quantitative descriptive analysis with a percentage. The result is that internal factors have an average (mean) of 81.20, a median value of 85, a value that often appears (mode) 93, a standard deviation of 14, a minimum value of 45, and a maximum value of 109. External factors had a mean of 61.04, median of 61, mode of 60, standard deviation of 11, minimum score of 28, and maximum score of 83. In conclusion based on these results, the survey shows that students' interest in learning soccer games in class VIII SMPN 3 Patokbuesi is in the good category.